Athletes with eating disorders: clinical-psychopathological features and gender differences - Rosinska, M.; Soós, D.; Gálvez Solé, L.; Ibáñez-Caparrós, A.; Thiel, A.; Zipfel, S.; Giel, K. E.; Granero, R.; Sánchez, I.; Pászthy, B.; Jiménez-Murcia, S.; Fernández-Aranda, F. (Journal of Eating Disorders, 2025)
Background Eating disorders (EDs) in the athlete population are often discussed in terms of comparing with non-athlete samples, however little is known regarding their gender clinical differences. Therefore, this study aimed to compare clinical and psychopathological features among athletes with an eating disorder (ED+A), non-athletes with an eating disorder (ED-A) and healthy controls (HCs), in addition to observing gender differences.